TInfusing Storytelling Activity to Foster Preschool Students’ Creativity at Al-Chasanah Foundation - Kristiawan, Nana; Utami, Amira (Society : Jurnal Pengabdian Masyarakat, 2025)
Storytelling is an activity that channels talents and interests in the art of speech. This service aims to provide storytelling training to improve teachers’ teaching creativity. The method used in this service is the lecture and discussion method with the author's active participation and simulation approach. Ten participants became the subject of this service, namely five kindergarten teachers, three family planning teachers, and two education staffs at Al-Chasanah kindergarten. Moreover, 60 kindergarten students participated in the storytelling simulation. The results of this training activity include; (1) The teacher's ability to deliver storytelling using puppet media, books, and recycled materials; (2) The teacher's ability to understand storytelling techniques. In this case, the teacher is able to distinguish between storytelling techniques with text and without text; (3) Knowledge of benefits in activities, among others. All in all, this service is found to enhance kindergarten teachers’ creativity through storytelling.